Komoditas Unggulan dan Identifikasi Sistem Agribisnis Perkebunan pada Sentra Produksi di Kecamatan Batulanteh Kabupaten Sumbawa - Junior, Adrian; Sudirman; Nurwahidah, Siti (AGRIFITIA : Journal of Agribusiness Plantation, 2025)
Plantation is one of the agricultural sectors that plays an important role in encouraging economic growth, especially in rural areas, through agribusiness-based farming activities. This research aims to identify superior commodities in the plantation sector and analyze the agribusiness system implemented in Sumbawa Regency. The research area was determined using a purposive sampling technique, starting from the district to the sub-district level which is the center for basic plantation crop production. The research will be carried out in July - August 2024. Determining the number of samples or respondents in the research, namely plantation agribusiness actors, took 30 respondents. The analysis method uses descriptive analysis methods, LQ (Location Quotient) analysis and SS (Shift Share) analysis. The research results show (1) There are 5 (five) basic commodities for the plantation sector in Sumbawa Regency, namely candlenut commodities, tamarind commodities, jatropha commodities, coffee commodities and cashew commodities. (2) The results of the analysis of the competitiveness of plantation commodities in Batulanteh District, Sumbawa Regency which have competitive competitiveness are candlenut commodities, coffee commodities and cashew commodities. (3) Results of identification of the plantation agribusiness sub-system in Sumbawa Regency, especially coffee and candlenut commodities which are the leading commodities in production centers in Batulanteh District, Sumbawa Regency : (a) The production facilities system, namely the provision of seeds, is still independent from harvested seeds, (b) sub-system of farming, namely cultivation is still non-technical on government forest land and private gardens, (c) processing sub-system is still simple and small scale, (d) The marketing sub system is still mostly in the form of primary products (for example coffee beans and candlenut seeds) farmers mostly sell to village and sub-district level collectors, (e) The institutional sub-system, namely extension workers, farmer groups and commercial banks, provides training to entrepreneurs in processing primary products into final products.